(3GdJbfjGJ GdMOjKI ddEfJGL GdJdaRjhfj h GdYed GdENHGQj aj GdbfhGJ GdaVGFjI (B/s - (3GdYRYRj, hOjYs ((3YeGf (B:s (3OGQGdjGRhQj GdYdejI ddfTQ h GdJhRjY ,s, 2022)
(3gPG GdcJGH jMGhd Gf jbOe bQGAI dhGbY GdJbfjGJ GdMOjKI GdeSJNOeI aj GdGfJGL GdJdaRjhfj h GdYed GdGNHGQj aj GdbfhGJ GdaVGFjI ef NdGd GQHYI aUhd h HGSdhH hGVM h HSjW jdGFe cGaI GdaFGJ GdeSJgOaI h jYjfgG Ydi GdGSJaGOI GdeKdi efg s
(3HHdjhZQGajG (B: 125-132s
Keywords: (3GdEYdGes; (3GdJdaRjhfs; (3GdbfhGJ GdENHGQjIs